PENGARUH PENGGUNAAN ANIMASI GAMBAR TERHADAP MINAT BELAJAR SISWA KELAS TINGGI SD INPRES 4/82 BAJOE KECAMATAN TANETE RIATTANG TIMUR KABUPATEN BONE - Ardandi Ardandi; Makmur Nurdin; Sudirman Sudirman (Sekolah Tinggi Pariwisata Mataram, 2022)
This research is a pre-experimental study that aims to determine the effect of using animated images on learning interest in high grade students of SD Inpres 4/82 Bajoe, Tanete Riattang Timur District, Bone Regency. The research approach is a quantitative approach. This type of research is pre-experimental research. Data obtained through tests and observations. The population in the study were all high grade students of SD Inpres 4/82 Bajoe for the academic year 2021/2022 totaling 41 students. The sample in the study amounted to 41 students. Data analysis techniques are Descriptive Statistical Analysis and Inferential Statistical Analysis. The results showed that before the use of high-grade animated images of SD Inpres 4/82 Bajoe was included in the sufficient category and after the use of high-grade animated images, SD Inpres 4/82 Bajoe was included in the good category and the learning interest of high-class students of SD Inpres 4/82 Bajoe was included in the category is very strong and there is a significant effect between the use of animated images and interest in learning in high grade students of SD Inpres 4/82 Bajoe, Tanete Riattang Timur District, Bone Regency.